PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI BEKERJA PEGAWAI DI LINGKUNGAN KANTOR PENGAWASAN DAN PELAYANAN BEA CUKAI TIPE MADYA PABEAN TANJUNG PERAK - Galih Setigi Al Hakim; Sri Rahayu; Rifda Fitrianty (MANAJEMEN DEWANTARA, 2026)
Purpose: This study aims to examine the effect of reward and punishment on employee work motivation at the Customs and Excise Supervision and Service Office, Tanjung Perak Middle-Type Customs Office. Research Method: This study used a quantitative survey approach. The population consisted of 377 employees, and 79 respondents were selected using the Slovin formula with a 10% margin of error. Primary data were collected through a five-point Likert-scale questionnaire and analyzed using validity testing, reliability testing, classical assumption testing, multiple linear regression, t-test, F-test, and coefficient of determination with SPSS 23. Result: The findings show that reward has a positive and significant effect on work motivation, and punishment also has a positive and significant effect on work motivation. Simultaneously, reward and punishment significantly affect employee work motivation, as indicated by F = 12.050 and p < 0.05. The model explains 24.1% of the variation in work motivation, while the remaining variation is explained by other factors outside this study.